Transient stability analysis of a new proposed hybrid PV-WTG microgrid for Tinghir power distribution - Hicham Stitou; Mohamed Amine Atillah; Abdelghani Boudaoud; Mounaim Aqil (International Journal of Applied Power Engineering (IJAPE), 2026)
This work focuses on the transient stability of a hybrid photovoltaic and wind turbine generator (PV-WTG) system at the Tinghir 225/60/11 kV substation in Morocco. Results were obtained by evaluating the effects of the proposed configuration on power angle, frequency, voltage, and fault-clearing times in the system. The study examined key disturbances, including abrupt loss of renewable energy and major electrical faults. Analysis using ETAP demonstrated a power angle change of -55 degrees, 20 degrees greater than the normal operating point, which can be caused by the loss of PV and approaches the IEEE Std 421.5 stability limit. The maximum voltage variation was 6.1% for the PV and 2.7% for the WTG, exceeding the IEC 60034-1 limits of ±5%. Another major finding of this analysis was that WTG loss induces frequency swings of 0.8 Hz and requires 10 to 15 seconds for recovery, indicating that low-inertia systems have insufficient inertia to return to steady state quickly. Therefore, the study demonstrates that adaptive control approaches must be used to achieve stable operation of hybrid connected microgrids. Using the time domain simulation (TDS) process, we calculated the critical clearing time (CCT) of 155 ms for 3-phase faults and 464 ms for line-to-ground faults, all of which are within the CCT limit set by IEEE Std 3002.2, and this confirms the necessity of urgent clearing of faults to maintain transient stability and demonstrates the need for fast protection and adaptive control in low-inertia systems, which is of particular concern in rural grids.